Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1139/f97-273
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature as a key factor determining the regional variability of the xenobiotic-inducible ethoxyresorufin-O-deethylase activity in the liver of dab (Limanda limanda)

Abstract: Water temperature exhibits a strong influence on the regional variability in activity of the 7-ethoxyresorufin-O-deethylase (EROD) in the liver of dab (Limanda limanda) from the German Bight during the spawning and postspawning seasons. The relationship between EROD activity and water temperature found in situ was, surprisingly, not masked by migrations of dab. Correlations between EROD activity and temperature could not be explained by a direct temperature effect in terms of temperature compensation. Instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…EROD) reactions, are well-documented (Kennedy et al 1991;Andersson and Forlin 1992). Acute temperature increase has been shown to result in an increase in benzo[a]pyrene hydroxylase activity and other P450-mediated transformations, however, given a sufficient acclimation period, activities return to baseline levels through compensatory mechanisms (Andersson and Koivusaari 1986;Gill and Walsh 1990;Andersson andForlin 1992, Kennedy andWalsh 1994;Lange et al 1998). Fish in the fasted and half-ration treatment groups exhibited peak EROD activities at week 6 which were greater than those noted in fish fed full-rations, before returning to basal levels by week 12.…”
Section: Erod Activitymentioning
confidence: 99%
“…EROD) reactions, are well-documented (Kennedy et al 1991;Andersson and Forlin 1992). Acute temperature increase has been shown to result in an increase in benzo[a]pyrene hydroxylase activity and other P450-mediated transformations, however, given a sufficient acclimation period, activities return to baseline levels through compensatory mechanisms (Andersson and Koivusaari 1986;Gill and Walsh 1990;Andersson andForlin 1992, Kennedy andWalsh 1994;Lange et al 1998). Fish in the fasted and half-ration treatment groups exhibited peak EROD activities at week 6 which were greater than those noted in fish fed full-rations, before returning to basal levels by week 12.…”
Section: Erod Activitymentioning
confidence: 99%
“…A strong influence of temperature on EROD activity has been shown to exist, although the temperature effect does not necessarily show a causal relationship but is rather coincidental with the state of maturity the fish have reached (see also Lange et al 1998). Krüner and Westernhagen (1995) showed experimentally that turbot (Scophthalmus maximus) displayed higher EROD activity with increasing temperatures, while Lange et al (1992) claimed higher EROD activity at lower temperatures in dab, and Sleiderink et al (1995b) even stated that in their investigations of EROD in North Sea dab the effect of water temperature was dominant over the effect of PCB contamination; EROD activity being higher at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The total concentration of P450 a sum parameter, frequently used and quite easy to determine, could be a screening method of contamination, mainly to polynuclear aromatic hydrocarbons (PAH), and planar polychlorinated biphenyls (PCB). Although some authors have shown that this method was less sensitive to induction than specifically inducible isoenzymes or their respective enzyme activities (Monod et al 1988, Lange et al, 1998. Standardizing analytical techniques is a crucial step that must be carried out before field application of biomarkers.…”
Section: Discussionmentioning
confidence: 99%